2009
DOI: 10.1093/rpd/ncp203
|View full text |Cite
|
Sign up to set email alerts
|

Indoor radon concentration measurement in the dwellings of district Poonch (Azad Kashmir), Pakistan

Abstract: The present study deals with measurement of indoor radon concentrations in dwellings of the district Poonch of the state of Azad Jammu and Kashmir, Pakistan. In this context, CR-39-based box-type radon detectors were installed in drawing rooms and bedrooms of 80 selected houses and were exposed to indoor radon for 3 months. After exposure, the CR-39 detectors were etched for 9 h in 6 mol NaOH at 70 degrees C and the observed track densities were related to radon concentrations. Measured indoor radon concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…The results of the study by Yousefi et al ( 31 ) in the City of Gorgan showed that the average and SD of the concentration of radon gas in the bedroom were 48.04±40.39 while they were 39.94±35.22 Bq/m 3 in the living room. Also, the results of a study by Denman & Rafigh using Cr-39 detectors in residential homes showed that the concentration of radon gas in the bedroom was higher than the concentration in the living room, which matches the results of the present study ( 40 , 41 ).…”
Section: Discussionsupporting
confidence: 91%
“…The results of the study by Yousefi et al ( 31 ) in the City of Gorgan showed that the average and SD of the concentration of radon gas in the bedroom were 48.04±40.39 while they were 39.94±35.22 Bq/m 3 in the living room. Also, the results of a study by Denman & Rafigh using Cr-39 detectors in residential homes showed that the concentration of radon gas in the bedroom was higher than the concentration in the living room, which matches the results of the present study ( 40 , 41 ).…”
Section: Discussionsupporting
confidence: 91%
“…This work deals with determination of radon exhalation from the locally mined export quality decorative stones and is a continuation of our previous studies (Rafique et al 2008(Rafique et al , 2010. The main objective of this work is to set up radon baseline data and to find out whether or not these decorative stones are safe to be exported for use in construction of buildings.…”
Section: Introductionmentioning
confidence: 99%
“…This study is a continuation of our previous published work. It is a step forward for setting the baseline data at radon Atlas for this part of world [18,19].…”
mentioning
confidence: 99%